MCM proteins are up-regulated in placentas of women with reduced insulin sensitivity - Bandres-Meriz, Julia; Sanz-Cuadrado, Marta Inmaculada; Hurtado de Mendoza, Irene; Majali-Martinez, Alejandro; Honeder, Sophie Elisabeth; Cindrova-Davies, Tereza; Birner-Gruenberger, Ruth; Dalgaard, Louise Torp; Desoye, Gernot (Bioscience reports, 2024)
In the first trimester of pregnancy the human placenta grows rapidly, making it sensitive to changes in the intrauterine environment. To test whether exposure to an environment in utero often associated with obesity modifies placental proteome and function, we performed untargeted proteomics (LC-MS/MS) in placentas from 19 women (gestational age 35–48 days, i.e. 5+0–6+6 weeks). Maternal clinical traits (body mass index, leptin, glucose, C-peptide and insulin sensitivity) and gestational age were recorded. DNA replication and cell cycle pathways were enriched in the proteome of placentas of women with low maternal insulin sensitivity. Driving these pathways were the minichromosome maintenance (MCM) proteins MCM2, MCM3, MCM4, MCM5, MCM6 and MCM7 (MCM-complex). These proteins are part of the pre-replicative complex and participate in DNA damage repair. Indeed, MCM6 and γH2AX (DNA-damage marker) protein levels correlated in first trimester placental tissue (r = 0.514, P<0.01). MCM6 and γH2AX co-localized to nuclei of villous cytotrophoblast cells, the proliferative cell type of the placenta, suggesting increased DNA damage in this cell type. To mimic key features of the intrauterine obesogenic environment, a first trimester trophoblast cell line, i.e., ACH-3P, was exposed to high insulin (10 nM) or low oxygen tension (2.5% O2). There was a significant correlation between MCM6 and γH2AX protein levels, but these were independent of insulin or oxygen exposure. These findings show that chronic exposure in utero to reduced maternal insulin sensitivity during early pregnancy induces changes in the early first trimester placental proteome. Pathways related to DNA replication, cell cycle and DNA damage repair appear especially sensitive to such an in utero environment.